PEDAGOGICAL FOUNDATIONS OF FORMING PATRIOTISM AND UNIVERSAL HUMAN VALUES IN PRIMARY SCHOOL EDUCATION (Web of Teachers: Inderscience Research, 2026)
This article provides a comprehensive analysis of the theoretical and practical foundations of developing patriotism, national identity, moral values, and universal human values in primary school education lessons. It emphasizes that the primary education stage is the most crucial period in the formation of a child’s personality, and the role and importance of education lessons in this process are examined from a scientific perspective. The article substantiates the effectiveness of using interactive methods in developing virtues such as love for the homeland, respect for historical heritage, tolerance, humanism, honesty, and solidarity in students. Additionally, it scientifically explains the impact of factors such as the teacher’s pedagogical skills, a student-centered approach, appropriate use of national traditions, and the suitability of educational materials to the age characteristics of students. The research results are enriched with methodological recommendations aimed at improving the educational process in primary education and contributing to the development of students as well-rounded individuals.